CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE IN INDIAN PRIVATE HEALTHCARE: A LITERATURE REVIEW AND CONCEPTUAL FRAMEWORK - Farooqui, Arshiya; John, Prof. (Dr.) Shibu; Raychaudhari, Dr. P.S. (South Eastern European Journal of Public Health, 2024)
Background Corporate governance has become essential to ensuring sustainability, accountability, and transparency in businesses, especially in the healthcare industry where operational and financial issues are complex. Objectives This paper aims to explore key factors that affect corporate governance, review the literature to identify research gaps and propose a conceptual framework linking corporate governance with the financial performance of healthcare organizations. Methods A comprehensive literature review was conducted using online databases like SCOPUS, Web of Science, Science Direct, and Jstor.PRISMA(Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed to illustrate the process of selecting studies for inclusion in a systematic review of corporate governance. 119 papers were extracted using keywords such as the board of directors, corporate governance, financial performance, hospitals, and healthcare financial performance, out of which 60 papers were finally analyzed. Key constructs such as Board Structure, Fairness, Transparency and Accountability, Internal Control Systems, Corporate Governance Initiatives, and Corporate Social Responsibility were identified. Results and Conclusion The results show how important governance tools are for improving hospital financial performance. Financial measures like return on equity and assets and governance procedures appear to be strongly correlated. The operational and financial challenges can be mitigated with the help of the suggested conceptual framework which places a strong emphasis on the integration of governance structures and performance measures. To further explore these findings in the context of Indian healthcare, more empirical study is advised.